Evaluación química del humus de lombriz roja californiana (Eisenia foetida), a partir de sustrato de cáscara de cacao y estiércol bovino - Mendoza Vintimilla, Erick Humberto (2019)
The objective of the research was to evaluate the chemical characteristics of the California red worm humus (Eisenia foetida) from cocoa shell and bovine manure, studying the effect of five treatments: 100% cocoa shell, 75% cocoa shell + 25% bovine manure, 50% cocoa shell + 50% bovine manure, 75% bovine manure + 25% cocoa shell and 100% bovine manure (control), each one replicating three times, giving a total of 15 experimental units. The experiment was conducted under the delineations of the DCA of a factor, using the InfoStat 2019 software for data analysis, measuring the effect on the variables: pH, organic matter, nitrogen, phosphorus and potassium. According to the statistical analysis, the best treatment was 75% bovine manure + 25% cocoa shell (T4), according to the results obtained in the ANOVA and Tukey mean test at 5% probability of error, performed at chemical parameters previously determined, however the only treatment that exceeded 15% improvement was T1 in terms of potassium compared to the control, so the hypothesis is accepted, demonstrating that the mixture between cocoa shell and bovine manure positively influences in the improvement of the chemical characteristics of the earthworm humus to be used as organic fertilizer.